A New Projection-Based Integrally Embedded Discrete Fracture Model and Its Application in Coupled Flow and Geomechanical Simulation for Fractured Reservoirs. (23rd February 2022) - Wu, Dawei; Di, Yuan; Wu, Yu-Shu
Abstract : The embedded discrete fracture model (EDFM) has been popular for the modeling of fractured reservoirs due to its flexibility and efficiency while maintaining the complex geometry of fracture networks. Though the EDFM has been validated for single-phase flow simulations, some recent cases show that the EDFM might result in apparent errors in multiphase flow situations. The projection-based embedded discrete fracture model (pEDFM) and the integrally embedded discrete fracture model (IEDFM) are two recently developed methods, which intend to improve the accuracy of the EDFM. In this study, a projection-based integrally embedded discrete fracture model (pIEDFM) is proposed, which combines the advantages of the pEDFM and the IEDFM. Similar to the pEDFM, the pIEDFM uses a kind of additional connections between fracture and nonneighboring matrix cells to obtain more physically authentic velocity fields. As a significant improvement, a semi-analytical cone-shaped pressure distribution that follows the IEDFM is adopted in the pIEDFM to capture the sharp pressure change near the fracture surfaces. Comparisons with benchmark results and explicit-fracture fine grid simulation results show that the pIEDFM provides accurate solutions using a moderate amount of grids. The proposed pIEDFM is also applied to coupled flow and geomechanical simulation for fractured reservoirs. Comparison of our coupled simulation results with that of the EDFM shows that the pIEDFM is applicable for the coupled simulation, and the different methods for matrix-fracture transmissibility between the pIEDFM and the EDFM may lead to deviations in stress fields predicted by geomechanical modeling, which eventually affects the oil production, water cut, and oil saturation profiles.